OPTIMALISASI PENYELENGGARAAN PERTAHANAN WILAYAH PERBATASAN PENDEKATAN HUMAN SECURITY DALAM RANGKA MENDUKUNG KETAHANAN WILAYAH KECAMATAN ENTIKONG, KABUPATEN SANGGAU, PROVINSI KALIMANTAN BARAT - _, Rahman (Jurnal Ketahanan Nasional, 2013)
This paper explained the optimization of institutional defense in Entikong. The qualitative data showed the defense establishment in regional border Entikong had not yet maximum due the lack of supervision on some remote areas, lack of order on freight traffic and the people who used traditional roads and also the lack of community involvement in regional resilience. There were also the lacks of basic facilities and infrastructures (transportation, electricity, clean water, and telecommunication), Indonesian people at border region economic dependency on Malaysia, the lack human resources quality and non-military defense software.Keywords: Defense Etablishment, Human Security, and Regional Resilience.